MANAJEMEN SUMBER DAYA PENDIDIK - Siswo Edi Wibowo; Supomo Kandar; Sumadi Sumadi (9 772338317006)
This research was aimed to analyze and describe the planning, provisioning, managing, supervising, resigning, and responsibilty of educator human resources at SMK Bina Latih Karya Bandar Lampung. This research method used the qualitative approach, it was because the data and information the writer collected were dominated and presented in verbal information and explanation that was not in numbers.The result of the research showed that; (1) planning of educator human resources was based on the numbers of student registration, (2) team decided to do recuitment, (3) managing of educator human resource done internally and externally, (4) supervising of educator human resources was done by bottom-up system, (5) resigning of the educator human resource had never been happened yet, (6) responsibility of the educator human resource was in the form of completing teaching learning documents, filling the regularity teaching journal, student academic achievement review, and how to interact with students.Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan perencanaan, pengadaan, pembinaan, pengawasan, pemberhentian, dan pertanggungjawaban sumber daya pendidik di SMK Bina Latih Karya Bandar Lampung. Metode penelitian ini menggunakan pendekatan kualitatif, karena data dan informasi yang peneliti kumpulkan lebih banyak berupa keterangan-keterangan dan penjelasan yang bukan berbentuk angka. Hasil penelitian ini menunjukkan bahwa: (1) Perencanaan sumber daya pendidik didasarkan atas banyaknya jumlah siswa pendaftar, (2) tim menentukan untuk melakukan perekrutan, (3) Pembinaan tenaga pendidik terdiri dari internal dan eksternal, (4) Pengawasan tenaga pendidik menggunakan sistem berjenjang, (5) Pemberhentian tenaga pendidik selama ini belum pernah terjadi, (6) Pertanggungjawaban tenaga pendidik berupa pemenuhan administrasi pelaksanaan KBM, keteraturan mengisi jurnal mengajar, peninjauan prestasi akademik siswa, dan cara tenaga pendidik menangani siswa.Kata kunci: manajemen, sekolah kejuruan, sumber daya pendidik